The Persistence Character and Math Processing Skills of Elementary School Students in Thematic Learning - Kamid; Dwi Agus Kurniawan; Rahmat Perdana; Bob Widodi; Elza Triani; Dila Yathasya; Putri Fadillah (Universitas Pendidikan Ganesha, 2023)
Mathematical process skills and study persistence are indicators of student learning success. Lack of persistence and mathematical process skills can hinder the distribution of knowledge in the learning process to students. So, it is important to conduct this research to measure the effect of mathematical process skills on students' persistence character. The survey method uses a mixed method with a sequential explanatory design. A simple random sampling technique was used as the sampling method in this study. In this study, hypothesis testing with a t-test and simple linear regression test is used as a method of data analysis. The collection method uses observation sheet research instruments, questionnaires, and interviews. This study found differences in students' mathematical processing skills and persistence in the multiplication and multiplication factor subjects in each elementary school. Furthermore, there is a significant influence between mathematical process skills on the character of student persistence in the thematic learning of the material factors of multiples and numbers. It was concluded that by knowing the effect of students' mathematical processing skills on their persistence character, educators should further maximize the learning process to train students' mathematical processing skills.